Functional Analyses of Cytokinesis Regulators in Bloodstream Stage Trypanosoma brucei Parasites Identify Functions and Regulations Specific to the Life Cycle Stage - Xuan Zhang (American Society for Microbiology, 2019)
ABSTRACT The early divergent protozoan parasite Trypanosoma brucei alternates between the insect vector and the mammalian hosts during its life cycle and proliferates through binary cell fission. The cell cycle control system in T. brucei differs substantially from that in its mammalian hosts and possesses distinct mitosis-cytokinesis checkpoint controls between two life cycle stages, the procyclic form and the bloodstream form. T. brucei undergoes an unusual mode of cytokinesis, which is controlled by a novel signaling cascade consisting of evolutionarily conserved protein kinases and trypanosome-specific regulatory proteins in the procyclic form. However, given the distinct mitosis-cytokinesis checkpoints between the two forms, it is unclear whether the cytokinesis regulatory pathway discovered in the procyclic form also operates in a similar manner in the bloodstream form. Here, we showed that the three regulators of cytokinesis initiation, cytokinesis initiation factor 1 (CIF1), CIF2, and CIF3, are interdependent for subcellular localization but not for protein stability as in the procyclic form. Further, we demonstrated that KLIF, a regulator of cytokinesis completion in the procyclic form, plays limited roles in cytokinesis in the bloodstream form. Finally, we showed that the cleavage furrow-localizing protein FRW1 is required for cytokinesis initiation in the bloodstream form but is nonessential for cytokinesis in the procyclic form. Together, these results identify conserved and life cycle-specific functions of cytokinesis regulators, highlighting the distinction in the regulation of cytokinesis between different life cycle stages of T. brucei. IMPORTANCE The early divergent protozoan parasite Trypanosoma brucei is the causative agent of sleeping sickness in humans and nagana in cattle in sub-Saharan Africa. This parasite has a complex life cycle by alternating between the insect vector and the mammalian hosts and proliferates by binary cell fission. The control of cell division in trypanosomes appears to be distinct from that in its human host and differs substantially between two life cycle stages, the procyclic (insect) form and the bloodstream form. Cytokinesis, the final step of binary cell fission, is regulated by a novel signaling cascade consisting of two evolutionarily conserved protein kinases and a cohort of trypanosome-specific regulators in the procyclic form, but whether this signaling pathway operates in a similar manner in the bloodstream form is unclear. In this report, we performed a functional analysis of multiple cytokinesis regulators and discovered their distinct functions and regulations in the bloodstream form.